Development of Student Worksheets Based on Project Based Learning on the Material 'Indonesia Kaya Budaya' for Class IV SDIT Tiara Islamic School Pekanbaru - Wahyuni, Yulia Septi; Suriadi, Hari; Deprizon; Miaz, Yalvema (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to develop a Student Worksheet (LKPD) based on Project-Based Learning (PjBL) integrated with Islamic values on the theme “Indonesia Kaya Budaya” for fourth-grade students at SDIT Tiara Islamic School Pekanbaru. The research employed the 4D development model (Define, Design, Develop, Disseminate), which includes needs analysis, design, expert validation, and limited trials. Data were collected through observations, validation questionnaires, practicality questionnaires, and student reflections. Expert validation results indicated that the LKPD falls into the "highly valid" category with an average score of 89.4%. A limited trial involving 10 students demonstrated active student engagement in project activities and an understanding of cultural and Islamic values. Teacher and student responses regarding the practicality of the product were also highly positive. The LKPD successfully facilitates contextual and religious thematic learning while strengthening students' character through the reflection of Islamic values. This product is deemed suitable as an alternative thematic learning medium in Islamic-based elementary schools.